Framework for activating temporary Waqf as contemporary social micro-financing tool in Malaysia. - Ghalia, Bouhedda; saheed, Abdullahi Busari (2018)
Temporary Waqf (Al-Waqf Al-Muʼaqat) is fast gaining momentum in contemporary financial transactions as a result of its validation by OIC-Fiqh Academy favoring the view of the Māliki’s school of law on the validity of temporary waqf. The research aims to develop an applicable framework for activating temporary waqf in Malaysian society. Despite the adoption of waqf in modern financial landscape, temporary waqf still lags behind perpetual waqf particularly with in Malaysia diverse market. Recently, the key statistic of household income & expenditure 2016, shows that the growth of poverty alleviation development program in Malaysia have improved by just 2% consequently because, there are large percentage of citizens who are financially excluded in accessing loans and benefits from banks and Takaful operators. These categories are either unemployed, aged or handicapped citizens which the temporary waqf can easily cater for. However, the Association of Valuers, (PEPS) of Malaysia have concurred with Bank Negara that unutilized properties within Malaysia is estimated as RM35.5bilions. These properties could have been employed for basic social financing among the financially excluded citizens. Hence, this study aims to explore the use of temporary waqf as a micro financing tool in potential areas such personal financing in education, health care and marriage contract. The study employs the inductive method in reviewing the available literature, and analytically examine the sharīʻah aspects of Certain waqf laws in in Johor, Selangor and Kelantan of Malaysia. Doing so, the framework will consider the possibility of extending the application of temporary waqf to all states within Malaysia. Therefore, the researchers deem it a matter of urgency to develop a framework for activation of temporary Waqf by mobilizing the use of unused assets and liquidity for providing primary health care services, funding education and aiding marriage consummation among Malaysian citizens.